Look alive twenty-five : a Stephanie Plum novel - Evanovich, Janet (New York : G.P. Putnam's Sons, an imprint of Penguin Random House LLC, 2018)
"Nothing's more Jersey than a good delicatessen. And if you're visiting Trenton, you can't do better than the Red River Deli. The coleslaw's edible and the oil in the deep fryer gets changed-eventually. It's a tribute to quality management, but that's now in jeopardy because the last three managers have vanished. The only clue to each disappearance is one shoe left behind. Stephanie Plum, Jersey girl and bounty hunter extraordinaire, is stepping into the manager's shoes ... well, shoe. The hottest detective on the force, Stephanie's boyfriend, Joe Morelli, is running down clues, and the always mysterious Ranger is sticking to Stephanie like pork roll to an egg sandwich. If Stephanie intends to avoid disappearing and hold on to 100 percent of her footwear, she has to do more than man the potato salad -- she needs to find out who took the previous victims. Each disappearance leads to more questions, but with Stephanie and Lula running the deli, the most pressing question remains, How many "I"s in salmonella?"--Front jacket flap.
Keywords: Plum, Stephanie -- (Fictitious character) -- Fiction; Women bounty hunters -- Fiction; Missing persons -- Investigation -- Fiction; Delicatessens -- Fiction; FICTION -- Women Sleuths. -- Women Sleuths; FICTION -- Humorous; New Jersey -- Fiction